2020
DOI: 10.1021/acs.jmedchem.0c01367
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Characterization of Cyclic Disulfide-Containing Peptide Analogs of the Multifunctional Opioid/Neuropeptide FF Receptor Agonists That Produce Long-Lasting and Nontolerant Antinociception

Abstract: In a previously described chimeric peptide, we reported that the multifunctional opioid/neuropeptide FF (NPFF) receptor agonist 0 (BN-9) produced antinociception for 1.5 h after supraspinal administration. Herein, four cyclic disulfide analogs containing l- and/or d-type cysteine at positions 2 and 5 were synthesized. The cyclized analogs and their linear counterparts behaved as multifunctional agonists at both opioid and NPFF receptors in vitro and produced potent analgesia without tolerance development. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
92
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(100 citation statements)
references
References 61 publications
6
92
2
Order By: Relevance
“…The present work suggests that d -type basic amino acids at position 2 of lactam bridge cyclic DN-9 analogues are more stable against enzymatic degradation in plasma. The present results are consistent with our recent study that the cyclization at positions 2 and 5 of BN-9 via disulfide linkages had no significant effects on plasma stability …”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…The present work suggests that d -type basic amino acids at position 2 of lactam bridge cyclic DN-9 analogues are more stable against enzymatic degradation in plasma. The present results are consistent with our recent study that the cyclization at positions 2 and 5 of BN-9 via disulfide linkages had no significant effects on plasma stability …”
Section: Discussionmentioning
confidence: 86%
“…In theory, supraspinal RF9 administration may prevent the anti-opioid action of the NPFF moiety of analogue 1 then exhibiting increased analgesic activity, which supports the NPFF agonism of analogue 1 . Consistent with this hypothesis, a recent study suggested that NPFF 2 R in the brain was primarily involved in antinociceptive augmentation after the co-injection of RF9 and the opioid/NPFF receptor multifunctional peptides in NPFF 2 –/– transgenic mice . However, peripheral administration of RF9 did not alter the antinociception induced by s.c. or p.o.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations